The Role of Responsive and Progressive Law In Addressing Legal Issues From A Sociological Perspective - Daryoko; Pangestika, Elza Qorina (Fakultas Hukum Universitas Widya Mataram, 2024)
As a State of law, the State of Indonesia as listed in article 1, paragraph 3, UUD 1945, whereas the law itself has three purposes: the certainty of law, the righteousness of law and the use of law, But of the three purposes of the law, justice is the primary purpose, rather than the use of law and the certainty of law. There are factors that have to be addressed in law enforcement in Indonesia, including weak substance of legislation, unprofessional law-enforcement machinery and moral deficits, as well as limited means and facilities. In dealing with the above legal problems, responsive legal theory and progressive law theory are expected to be able to provide the solution.